2022
DOI: 10.1371/journal.pone.0262906
|View full text |Cite
|
Sign up to set email alerts
|

The impact of a competitive event and the efficacy of a lactic acid bacteria-fermented soymilk extract on the gut microbiota and urinary metabolites of endurance athletes: An open-label pilot study

Abstract: Diet and exercise can alter the gut microbiota, but recent studies have assessed the impact of athletic competition on gut microbiota and host metabolites. We designed an open-label pilot study to investigate the effects of both official competition and a multi-strain lactic acid bacteria-fermented soymilk extract (LEX) on the gut microbiota in Japanese college endurance athletes. The analysis of fecal 16S rRNA metagenome and urinary metabolites was used to identify changes in gut microbiota composition and ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 48 publications
0
17
0
Order By: Relevance
“…An association between whey protein intake and the β-diversity of the adult gut virome was found, while no major changes in the functional activity of the gut microbiota were determined, with the exception of urinary levels of trimethylamine N-oxide (TMAO) and phenylacetylglycine (PAG) excretion. Similarly, Moitinho-Silva et al elucidated taxonomic differences, a significant increase in lymphocytes and a decrease in mean corpuscular haemoglobin concentration in healthy sedentary adults exposed to strength training [23] . No change in dietary patterns towards the end of the intervention period and after it was observed.…”
Section: The Association Of Gut Microbes With Sports Performancementioning
confidence: 87%
See 2 more Smart Citations
“…An association between whey protein intake and the β-diversity of the adult gut virome was found, while no major changes in the functional activity of the gut microbiota were determined, with the exception of urinary levels of trimethylamine N-oxide (TMAO) and phenylacetylglycine (PAG) excretion. Similarly, Moitinho-Silva et al elucidated taxonomic differences, a significant increase in lymphocytes and a decrease in mean corpuscular haemoglobin concentration in healthy sedentary adults exposed to strength training [23] . No change in dietary patterns towards the end of the intervention period and after it was observed.…”
Section: The Association Of Gut Microbes With Sports Performancementioning
confidence: 87%
“…With regard to Dorea longicatena, this taxon is associated with insulin sensitivity [17,33] . In addition, high abundances of Lachnospiraceae were determined in marathon runners and skiers [22] , while Coprococcus, Parasutterella genera and Ruminococcaceae family were increased in physically active individuals [23] .…”
Section: The Association Of Gut Microbes With Sports Performancementioning
confidence: 98%
See 1 more Smart Citation
“…Glycosaminoglycan Degradation Pathway Components Glycosaminoglycans (GAGs) are a major component of the animal's extracellular matrix and are degraded by some bacteria, such as probiotics [53]. In a previous study, the abundance of Parabacteroides and P. disstasonis was reported to be relatively low in obese, inflammatory bowel disease (IBD) patients, and to be abundant in a group of patients with hyperglycemic improvement [54,55]. In this study, galacto-oligosaccharides, a prebiotic contained in FRG, promote the growth of beneficial bacteria in the gut.…”
Section: Discussionmentioning
confidence: 99%
“…Sixteen studies found significant differences in microbial diversity 47,49,62,[74][75][76]79,80,51,52,[54][55][56][57][58]61 and 13 in the abundance of specific microbial taxa 47,52,78,79,104,53,[55][56][57][58][74][75][76] between athletes vs. non-athletes, professional vs. amateur or athletes from different sports. Three studies detected significant differences in alpha-diversity 89,90,92 , while 8 studies described significant changes in the relative abundance of certain bacteria after acute PA interventions 23,86,87,[89][90][91][92][93] . Seventeen studies detected significant differences in alphaand/or beta-diversity 94,95,115,[117][118][119][120]123,125,98,101,…”
Section: General Overviewmentioning
confidence: 99%